SUDDEN GAINS IN PROLONGED EXPOSURE AND SERTRALINE FOR CHRONIC PTSD. Issue 7 (30th April 2013) - Jun, Janie J.; Zoellner, Lori A.; Feeny, Norah C.
<x xml:space="preserve">Abstract</x> Background Sudden gains are significant, rapid improvements in symptoms, larger than typical between‐session symptom reduction.[8] Sudden gains in a large sample of individuals with posttraumatic stress disorder (PTSD) have not been studied, and only one study has looked at it in pharmacotherapy, but not in PTSD. In the present study, we examined the occurrence of sudden gains in psychotherapy, specifically prolonged exposure (PE), and pharmacotherapy, specifically sertraline, for chronic PTSD. Method Sudden gains in PTSD symptoms (PTSD symptom scale self‐report[25]) were assessed in 200 individuals with PTSD during 10 weeks of PE or sertraline. Results Individuals in both PE (42.2%) and sertraline (31%) exhibited sudden gains. Individuals in PE made more gains toward the end of treatment (7.2%) than sertraline (2%, OR = 3.82). However, individuals in sertraline made larger gains during early treatment (M = 18.35, SD = 8.15) than PE (M = 12.53, SD = 5.16, d = .85). Notably, those on sertraline were more likely to exhibit a reversal of sudden gains than those in PE (OR = .23). Pointing to clinical significance, the presence of a sudden gain was associated with better reduction in symptoms from pre‐ to posttreatment (β = −.49). Conclusions Individuals in both PE and sertraline experienced gains, though sertraline was associated with earlier large but reversible gains, and PE was associated with later gains. This differential pattern of discontinuous change highlights potential differential mechanism for these therapies and marks important transition points for further detailed analyses of change mechanisms.